A breath of fresh air: The effect of public smoking bans on Indigenous youth. (15th April 2021) - Daley, Angela; Rahman, Muntasir; Watson, Barry
Abstract: In general, past studies have estimated the average effect of public smoking bans on youth, ignoring differences across sub‐populations. We extend the literature by considering Indigenous youth, who are a vulnerable and previously unexamined group (however, our analysis excludes First Nations youth who live on reserve). We also consider previously unexamined outcomes among youth: self‐assessed health and subjective well‐being. Our difference‐in‐differences estimates from Canada indicate that public bans reduced youth smoking and second‐hand exposure in public places, on average. There was no displacement on the extensive margin, but the bans increased the number of people who smoke in the homes of youth, conditional on the presence of smokers in the household. Beyond average effects, however, we find that public bans reduced second‐hand exposure in the homes of Indigenous youth (particularly Métis youth), on the extensive and intensive margins. The same youth experienced concurrent improvements in self‐assessed health and life satisfaction. We conclude that public bans mitigate disparities in health and well‐being between Indigenous and non‐Indigenous youth, but the extent varies across Indigenous sub‐populations, even within a particular country.